Normative MRI, ultrasound and muscle functional MRI findings in the forearms of asymptomatic elite rowers. Issue 2 (February 2016) - Drew, Michael K.; Trease, Larissa; Caneiro, J.P.; Hooper, Ivan; Ooi, Chin-Chin; Counsel, Peter; Connell, David A.; Rice, Anthony A.; Knight, Emma; Hoy, Gregory; Lovell, Gregory
Abstract: Objectives: Forearm injuries are common and debilitating to elite rowers. Chronic exertional compartment syndrome, intersection syndrome and proximal radial bone stress injuries have been documented in this population. This paper explores the imaging findings related to these conditions in asymptomatic elite rowers. Design: Observational study. Methods: 19 asymptomatic senior elite and under-23 rowers currently competing at National level or above underwent ultrasound (US), Magnetic Resonance Imaging (MRI) and muscle functional MRI evaluation of their forearms. A comprehensive evaluation sheet identifying characteristics of bone stress, intersection syndrome and chronic exertional compartment syndrome was utilised based on a literature search and review by senior clinicians working with this population. Results: Peritendinous fluid of Extensor Carpi Radialis Longus ( n  = 10, 53%) or Extensor Carpi Radialis Brevis ( n  = 6, 32%) was a common finding on US. MRI had a higher rate of identification than US. Extensor Digitorum (Coeff = −1.76, 95%CI −3.04 to −0.49), Flexor Carpi Radialis (Coeff = −2.86, 95%CI −5.35 to −0.38) and Flexor Carpi Ulnaris (Coeff = −3.31, 95%CI −5.30 to −1.32), Pronator Teres (Coeff = −3.94, 95%CI −6.89 to −0.99), and Supinator (Coeff = −168, 95%CI −3.28 to −0.02) showed statistically significant changes immediately post-exercise. Mild proximal radial marrow hyperintensity was present ( n  = 15, 78.9%) with three participants (15.8%) also having mild periosteal oedema of the radius. Conclusions: Imaging findings commonly seen in symptomatic populations are observed in elite, asymptomatic rowers. Care should be taken when diagnosing bone stress injuries, intersection syndrome and compartment syndrome on imaging findings alone. Data presented can be utilised as a normative dataset for future case studies.